Medidas de urgência em sede recursal - Santos, Regiane Martins dos (2015)
The present task has the intention to present, analytically, the existing urgent measures in the Brazilian law, highlighting its use under appellate level. Begins with the conceptualization of the precautionary measure institutes, with the anticipation of the legal protection and the injunctions, going by the analysis of its peculiarities, distinctions and similarities. Then, the characteristics features of each guardianship analyzed in this study, highlighting its requirements and entering slowly in its peculiarities. Subsequently, the study addresses the filing of such measures on appellate headquarters, presenting the general theory of resources for, then, treat more specifically the use of the emergency measures also in this procedural sphere. Still, the peculiarities surrounding the new system of emergency measures under the new Code of Civil Procedure project are highlighted. Finally, the conclusions of the study are brought, presenting the corollary of the analysis and showing the most notable similarities and differences about the displayed topic